2018
DOI: 10.1016/j.bjae.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Emergence delirium after paediatric anaesthesia: new strategies in avoidance and treatment

Abstract: ED is common in preschool children undergoing general anaesthesia with sevoflurane. Symptoms include agitation, hyperactivity with flailing movements, confusion, and failure to recognize/engage with people and the surroundings. ED has known risk factors that include the use of short-acting volatile agents. The use of TIVA with propofol reduces the risks of ED. Treatment is largely drug based and should be undertaken if there is a potential risk of self-injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 18 publications
2
36
1
Order By: Relevance
“…The incidence of emergence agitation is two to three times more common in children than in adults. 26 Our meta-analysis showed that IV clonidine premedication produced an 11% lower incidence of emergence agitation than a placebo. Ydemann et al 27 conducted…”
Section: Ta B L E 3 Results Of Subgroup Analysesmentioning
confidence: 77%
“…The incidence of emergence agitation is two to three times more common in children than in adults. 26 Our meta-analysis showed that IV clonidine premedication produced an 11% lower incidence of emergence agitation than a placebo. Ydemann et al 27 conducted…”
Section: Ta B L E 3 Results Of Subgroup Analysesmentioning
confidence: 77%
“…This is higher than that quoted in the pediatric dental surgery population of between 13% and 29% 13,18,19 . Our entire study population comprised patients in the preschool group undergoing sevoflurane volatile anesthesia, both of which are established risk factors for ED 2,8,9 . The patients with ED in our study had a mean age of 3.8 years.…”
Section: Discussionmentioning
confidence: 76%
“…ED is a well‐described complication in pediatric anesthesia, more often occurring following short surgical procedures using volatile anesthetics with a rapid recovery profile 8 . The incidence of ED ranges from 10%‐80% 2 with most studies suggesting an incidence of 20% 9 . Inconsistent definitions, different scoring systems and different threshold values for ED contribute to the wide incidence 2 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations